LEARNING HOW TO BE POLITE THROUGH A MOVIE: A CASE ON BROWN AND LEVINSONâS POLITENESS STRATEGIES - Roita Angel Isabella; Eni Julita Br. Munthe; Dian Jessica Noventy Sigalingging; Ridwin Purba; Herman Herman (Universitas Kuningan, 2022)
Â This research discusses politeness strategies at the Tinkerbell movie. The purpose of this study is to analyze the types of politeness strategies, to determine the most dominant types of politeness strategies and to determine the factors that influence the selection of politeness strategies contained in the Tinkerbell Film. This research uses theory by Brown and Levinson (1987). The research method is descriptive qualitative research with content analysis, because the data are collected from documents. There are several steps in collecting data, such as: searching, downloading, watching and listening, transcribing. The results showed 20 politeness strategies found in Tinkerbell Movie, such us: bald on-record 2 (10%), positive politeness 13 (65%), negative politeness 3 (15%), and off-record 2 (10%). The most dominant type of politeness strategy found in Tinkerbell movie is positive politeness. Factors that influence the selection of politeness strategies contained in the Tinkerbell movie are circumstances. Circumstances related to sociological variables included relative power of 6 (30%) and social distance of 14 (70%). Relative power (P) uses a greater degree of politeness with other people who have higher power or authority. Social distance (D) is seen as a composite of psychological factors such as status and age. In conclusion, with this research we must be careful when using language to communicate with other people so that the conversation goes well. Keywords: pragmatics; politeness strategies; movie. Â